Answer:
Step-by-step explanation:
Answer: see proof below
<u>Step-by-step explanation:</u>
Given: A + B + C = π → C = π - (A + B)
→ sin C = sin(π - (A + B)) cos C = sin(π - (A + B))
→ sin C = sin (A + B) cos C = - cos(A + B)
Use the following Sum to Product Identity:
sin A + sin B = 2 cos[(A + B)/2] · sin [(A - B)/2]
cos A + cos B = 2 cos[(A + B)/2] · cos [(A - B)/2]
Use the following Double Angle Identity:
sin 2A = 2 sin A · cos A
<u>Proof LHS → RHS</u>
LHS: (sin 2A + sin 2B) + sin 2C
![\text{Sum to Product:}\qquad 2\sin\bigg(\dfrac{2A+2B}{2}\bigg)\cdot \cos \bigg(\dfrac{2A - 2B}{2}\bigg)-\sin 2C](https://tex.z-dn.net/?f=%5Ctext%7BSum%20to%20Product%3A%7D%5Cqquad%202%5Csin%5Cbigg%28%5Cdfrac%7B2A%2B2B%7D%7B2%7D%5Cbigg%29%5Ccdot%20%5Ccos%20%5Cbigg%28%5Cdfrac%7B2A%20-%202B%7D%7B2%7D%5Cbigg%29-%5Csin%202C)
![\text{Double Angle:}\qquad 2\sin\bigg(\dfrac{2A+2B}{2}\bigg)\cdot \cos \bigg(\dfrac{2A - 2B}{2}\bigg)-2\sin C\cdot \cos C](https://tex.z-dn.net/?f=%5Ctext%7BDouble%20Angle%3A%7D%5Cqquad%202%5Csin%5Cbigg%28%5Cdfrac%7B2A%2B2B%7D%7B2%7D%5Cbigg%29%5Ccdot%20%5Ccos%20%5Cbigg%28%5Cdfrac%7B2A%20-%202B%7D%7B2%7D%5Cbigg%29-2%5Csin%20C%5Ccdot%20%5Ccos%20C)
![\text{Simplify:}\qquad \qquad 2\sin (A + B)\cdot \cos (A - B)-2\sin C\cdot \cos C](https://tex.z-dn.net/?f=%5Ctext%7BSimplify%3A%7D%5Cqquad%20%5Cqquad%202%5Csin%20%28A%20%2B%20B%29%5Ccdot%20%5Ccos%20%28A%20-%20B%29-2%5Csin%20C%5Ccdot%20%5Ccos%20C)
![\text{Given:}\qquad \qquad \quad 2\sin C\cdot \cos (A - B)+2\sin C\cdot \cos (A+B)](https://tex.z-dn.net/?f=%5Ctext%7BGiven%3A%7D%5Cqquad%20%5Cqquad%20%5Cquad%202%5Csin%20C%5Ccdot%20%5Ccos%20%28A%20-%20B%29%2B2%5Csin%20C%5Ccdot%20%5Ccos%20%28A%2BB%29)
![\text{Factor:}\qquad \qquad \qquad 2\sin C\cdot [\cos (A-B)+\cos (A+B)]](https://tex.z-dn.net/?f=%5Ctext%7BFactor%3A%7D%5Cqquad%20%5Cqquad%20%5Cqquad%202%5Csin%20C%5Ccdot%20%5B%5Ccos%20%28A-B%29%2B%5Ccos%20%28A%2BB%29%5D)
![\text{Sum to Product:}\qquad 2\sin C\cdot 2\cos A\cdot \cos B](https://tex.z-dn.net/?f=%5Ctext%7BSum%20to%20Product%3A%7D%5Cqquad%202%5Csin%20C%5Ccdot%202%5Ccos%20A%5Ccdot%20%5Ccos%20B)
![\text{Simplify:}\qquad \qquad 4\cos A\cdot \cos B \cdot \sin C](https://tex.z-dn.net/?f=%5Ctext%7BSimplify%3A%7D%5Cqquad%20%5Cqquad%204%5Ccos%20A%5Ccdot%20%5Ccos%20B%20%5Ccdot%20%5Csin%20C)
LHS = RHS: 4 cos A · cos B · sin C = 4 cos A · cos B · sin C ![\checkmark](https://tex.z-dn.net/?f=%5Ccheckmark)
Answer:
52
Step-by-step explanation:
4(4)+6(9)
16+36
52
A + E + N = 122
E = 2N
A = 7 + E....A = 7 + 2N
(7 + 2N) + 2N + N = 122
5N + 7 = 122
5N = 122 - 7
5N = 115
N = 115/5
N = 23 <== North America
E = 2N
E = 2(23)
E = 46 <== Europe
A = 7 + E
A = 7 + 46
A = 53 <=== Africa
Just find the base area then multiply it by the height.
so here for the base area we can divide it in 2 parts 6x6 + 2x1
which the total is 38
then multiply 38 by 1, which is the height, so it's 38